Probiotic Weisella paramesenteroides on enteropathogenic E. coli-induced diarrhea - Aslinar Aslinar; Yusri Dianne Jurnalis; Endang Purwati; Yorva Sayoeti (Paediatrica Indonesiana, 2014)
Background Enteropathogenic Escherichia coli (EPEC) is a causative agent of intestinal inflammation and microfloral imbalance, leading to diarrhea. The presence of tumor necrosis factor-α (TNF-α) in the feces is an indicator of inflammation in the intestinal mucosa. Dadih, (local made of fermented buffalo milk), contains probiotics and is widely consumed by the people in West Sumatera, Indonesia. Weisella paramesenteroides, a probiotic lactic acid bacteria (LAB), has been isolated from dadih and is believed to be useful for improving intestinal microflora balance and inhibiting the activity of harmful microbes. Objective To determine the efficacy of W. paramesenteroides administration in various doses and durations on bowel frequency, stool’s TNF-α levels, and intestinal microflora balance on mice with EPEC-induced diarrhea. Method This randomized experimental animal study examined two factors relating to the effects of W. paramesenteroides on EPEC-induced diarrhea, namely doses of probiotics (factor A), and durations of observation (factor B). The subjects consisted of 100 male white mice (Mus musculus) aged 8 weeks, with weights of 25-30 grams. The outcomes measured were bowel frequency, stool’s TNF-α levels, and the balance of intestinal microflora on mice with EPEC-induced diarrhea. Subjects were divided into 5 groups: the negative control group (received neither EPEC nor probiotic), positive control group (received only EPEC), and three experimental groups (received EPEC and different doses of W. paramesenteroides ). Probiotics were given twice at the 12-hours and 24-hours for the experimental groups, while the durations of observation conssited of baseline, 12 hours, 24 hours, and 36 hours. Results After 36 hours, subjects with EPEC-induced diarrhea who received W. Paramesenteroides administration in doses of 2 x 108 (A3), were found to have the largest decline of mean defecation (a 4.4-fold decline) and the largest decline of stool’s mean TNF-α levels (48.3 pg/mL), compared to the positive control group, and other experimental groups who received higher doses of probiotics.